Recent insight into the advances and prospects of microbial lipases and their potential applications in industry - Eskandari, Azadeh; Thean, Chor Leow; Abdul Rahman, Mohd Basyaruddin; Oslan, Siti Nurbaya (Hemeroteca Científica Catalana, 2024)
Enzymes play a crucial role in various industrial sectors. These biocatalysts not only ensure sustainability and safety but also enhance process efficiency through their unique specificity. Lipases possess versatility as biocatalysts and find utilization in diverse bioconversion reactions. Presently, microbial lipases are gaining significant focus owing to the rapid progress in enzyme technology and their widespread implementation in multiple industrial procedures. This updated review presents new knowledge about various origins of microbial lipases, such as fungi, bacteria, and yeast. It highlights both the traditional and modern purification methods, including precipitation and chromatographic separation, the immunopurification technique, the reversed micellar system, the aqueous two-phase system (ATPS), and aqueous two-phase flotation (ATPF), moreover, delves into the diverse applications of microbial lipases across several industries, such as food, vitamin esters, textile, detergent, biodiesel, and bioremediation. Furthermore, the present research unveils the obstacles encountered in employing lipase, the patterns observed in lipase engineering, and the application of CRISPR/Cas genome editing technology for altering the genes responsible for lipase production. Additionally, the immobilization of microorganisms’ lipases onto various carriers also contributes to enhancing the effectiveness and efficiencies of lipases in terms of their catalytic activities. This is achieved by boosting their resilience to heat and ionic conditions (such as inorganic solvents, high-level pH, and temperature). The process also facilitates the ease of recycling them and enables a more concentrated deposition of the enzyme onto the supporting material. Consequently, these characteristics have demonstrated their suitability for application as biocatalysts in diverse industries.